2022
DOI: 10.1155/2022/1052166
|View full text |Cite
|
Sign up to set email alerts
|

hUC-MSCs Attenuate Acute Graft-Versus-Host Disease through Chi3l1 Repression of Th17 Differentiation

Abstract: Mesenchymal stem cells (MSCs) have already demonstrated definitive evidence of their clinical benefits in acute graft-versus-host disease (aGvHD) and other inflammatory diseases. However, the comprehensive mechanism of MSCs’ immunomodulation properties has not been elucidated. To reveal their potential immunosuppressive molecules, we used RNA sequencing to analyze gene expression in different tissue-derived MSCs, including human bone marrow, umbilical cord, amniotic membrane, and placenta, and found that chiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…In this study the authors showed that, though the priming treatment induced the increase of CCL2 and MHCI/II expression in IFN-γ-primed MSCs, it inhibited manifestations of autoimmune encephalomyelitis while keeping their immunogenicity low. The use of IFN-γ- or TNF-α-primed MSCs has also been shown to attenuate symptoms of GVHD[ 101 , 103 ]. In these cases, in the first study it was shown that therapeutic effects of MSCs were mediated by overproduction of IDO induced through the IFN-γ-JAK-STAT1 pathway[ 101 ].…”
Section: Therapeutic Properties Of Primed Mscs In Preclinical Modelsmentioning
confidence: 99%
“…In this study the authors showed that, though the priming treatment induced the increase of CCL2 and MHCI/II expression in IFN-γ-primed MSCs, it inhibited manifestations of autoimmune encephalomyelitis while keeping their immunogenicity low. The use of IFN-γ- or TNF-α-primed MSCs has also been shown to attenuate symptoms of GVHD[ 101 , 103 ]. In these cases, in the first study it was shown that therapeutic effects of MSCs were mediated by overproduction of IDO induced through the IFN-γ-JAK-STAT1 pathway[ 101 ].…”
Section: Therapeutic Properties Of Primed Mscs In Preclinical Modelsmentioning
confidence: 99%
“…According to our previous RNA sequencing results for different sources of MSCs, including MSCs derived from human umbilical cord, amniotic membrane, placenta, and bone marrow [ 13 ], we found that TGFBI, an extracellular matrix protein induced by TGF-β signaling, was highly expressed in human umbilical cord-derived hMSCs (hUC-MSCs) (Supplemental Fig. 1).…”
Section: Resultsmentioning
confidence: 87%
“…In addition, different sources of mesenchymal stem/stromal cells have distinct characteristics [ 11 , 12 ]. To identify the immune functional properties from different sources of MSCs, RNA sequencing was performed on MSCs isolated and cultured from umbilical cord, amniotic membrane, placenta, and bone marrow [ 13 ]. Our data showed that transforming growth factor beta-induced gene (TGFBI) was highly expressed in MSCs obtained from human umbilical cord.…”
Section: Introductionmentioning
confidence: 99%
“…By increasing the generation of IL-10 and PGE2 and decreasing that of IL-17, IL-22, and IFN-y, MSCs prevent the differentiation of Th17. 75,76 T A B L E 2 MSCs-derived exosomes in animal models with deregulated immune response. their cytokine composition and raises the possibility that BM-MSCs may impact Th17 lymphocytes' biological functions.…”
Section: Adaptive Immune Systemmentioning
confidence: 99%
“…It has been demonstrated that MSCs influence T‐cells and other members of the adaptive immune system through paracrine secretion. By increasing the generation of IL‐10 and PGE2 and decreasing that of IL‐17, IL‐22, and IFN‐y, MSCs prevent the differentiation of Th17 75,76 . Studies combining bone marrow (BM)‐MSCs with T cells in cocultivation have shown that cytokine priming of BM‐MSCs affects their cytokine composition and raises the possibility that BM‐MSCs may impact Th17 lymphocytes' biological functions 77 .…”
Section: Mscs and Their Anti‐inflammatory Rolesmentioning
confidence: 99%